2015
DOI: 10.1103/physreve.92.063008
|View full text |Cite
|
Sign up to set email alerts
|

Between giant oscillations and uniform distribution of droplets: The role of varying lumen of channels in microfluidic networks

Abstract: The simplest microfluidic network (a loop) comprises two parallel channels with a common inlet and a common outlet. Recent studies that assumed a constant cross section of the channels along their length have shown that the sequence of droplets entering the left (L) or right (R) arm of the loop can present either a uniform distribution of choices (e.g., RLRLRL...) or long sequences of repeated choices (RRR...LLL), with all the intermediate permutations being dynamically equivalent and virtually equally probabl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Although these authors used droplets (rather than RBCs) and significantly wider micro-channels, the results are applicable to the microcirculation due to the dynamic similarity of the systems. These studies provided evidence that small changes of cross-section13 or length20 along specific channels can enable/disable specific patterns of droplets in a network. Nevertheless, it should be kept in mind that the physics of droplets is inherently different from RBCs due to intrinsic mechanical properties of the RBC membrane able to support shear29.…”
mentioning
confidence: 94%
See 3 more Smart Citations
“…Although these authors used droplets (rather than RBCs) and significantly wider micro-channels, the results are applicable to the microcirculation due to the dynamic similarity of the systems. These studies provided evidence that small changes of cross-section13 or length20 along specific channels can enable/disable specific patterns of droplets in a network. Nevertheless, it should be kept in mind that the physics of droplets is inherently different from RBCs due to intrinsic mechanical properties of the RBC membrane able to support shear29.…”
mentioning
confidence: 94%
“…The basic mechanisms have been extensively investigated in single bifurcations6891011. In networks of bifurcating (diverging and converging) vessels, RBC dynamics becomes more complex and often counter-intuitive5121314151617. Computational simulations818 of blood rheology in microcirculatory networks of the rat mesentery have shown that blood flow can undergo spontaneous, self-sustained oscillations in capillaries under steady conditions without any active biological regulation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The various observations confirmed that in the bifurcating junction a single short droplet is directed into the channel with the higher flow velocity (Parthiban and Khan 2013;Wang and Vanapalli 2014;Cybulski et al 2015). As the droplet changes the resistance of the flow in a channel, the distribution of flows between the two outputs will depend on the current number of droplets in each of the branches.…”
Section: Observations Of the Effect Of Modification J1 On The Flow Ofmentioning
confidence: 56%